Hvad hed Aquilonius’ fader? En fejlfortolkning af forfatterens latiniserede efternavn - Kølkær, Mikkel (Danske Studier, 2025)
In this short paper, I investigate the historical sources and explain why there has been doubt in the literature about the name of the father of the Danish Neo-Latin author Bertel Knudsen Aquilonius (1588-1650).